ANALISIS KREATIVITAS MAHASISWA PGSD DALAM MEMBUAT KOMIK DIGITAL MENGGUNAAN MODEL PEMBELAJARAN PROJECT BASED LEARNING - Feby Inggriyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Professional educators need to have skills in designing innovative learning and adapting it to the characteristics of students and developments in the 21st century. However, the reality in the field is that many educators are not yet technologically literate and do not use digital media in their learning. Therefore, prospective elementary school teachers need to be given creative thinking skills in designing digital comic learning media. This research uses descriptive quantitative which aims to analyze student creativity in making digital comics after implementing the project based learning model. The data collection techniques used were observation, interviews and documentation in the form of photos and videos. The subjects of this research were fifth semester students of the Primary School Teacher Education Study Program for the 2023/2024 academic year. The dimensions of creativity in this research are fluency of thinking, flexibility of thinking, elaboration and originality. The data in this research was analyzed descriptively with the results of the implementation of learning taking place effectively and conducively and student creativity in making digital comics was in the good category at 79.5%. Thus, the project based learning model is able to make PGSD students think creatively in designing and making digital comic media in learning to improve students' reading comprehension skills. Keywords: digital comics, student creativity, project based learning model